Стабилизация заднего хода автопоезда с двухосным прицепом методом линеаризации обратной связью по состоянию - Скляренко, Евгений Геннадиевич; Шумахер, Вальтер (НТУ "ХПИ", 2010)
This paper presents the design of a stabilization and tracking control for the backward motion for a truck with a single off-axle hitched trailer, whose kinematic model is not exactly input-state linearizable. The designed nonlinear control low is based on inputstate linearization of the auxiliary kinematic model, which can indeed be exactly linearized and whose behavior satisfies a good performance in the region of operation. It yields a locally asymptotically stable closed-loop system with both a positive and negative shift direction of the hitching point from the truck’s rear axle.
Stabilization of the backward motion for truck and trailer based on input-state linearization
Keywords: устойчивость асимптотическая; тягач; модель кинематическая; диффеоморфизм; моделирование компьютерное